Diseño de rutas para el mejoramiento del proceso de abastecimiento de leche en el municipio de Uramita (Antioquia) usando sistemas de información geográfica (2017)
The research aimed to design and develop routes for the supply of raw milk in the town Uramita (Antioquia), in order to propose improvements in the current process and increase profits for farmers by offering more volume to industries. The problem was identified, analysed and described the current state of the supply process with the aim of formulating possible solutions or improvements. To solve this problem: Improve the supply route for the collection of milk from the farmers that generates a better use of this and in turn increase the profits; A survey of the collection tanks and producers was carried out, determining the capacities of the tanks, transportation costs and location using the global positioning system (GPS). This information allowed to locate the current collection system. Using geographic information systems (GIS) were modeled and showed how the routes change by reducing the number of vehicles taking into account a 24-hour time window where the milk remains in good condition and in turn generates a decrease in the costs of transport. Finally, the current result with the improvement proposal was analysed and compared from KPI, validating that the obtained results generate an improvement in the process.